1996
DOI: 10.1016/s0092-8674(00)81092-2
|View full text |Cite
|
Sign up to set email alerts
|

Active and Inactive Protein Kinases: Structural Basis for Regulation

Abstract: This review will focus on the role of the activation segment in the mediation of these different aspects of and David J. Owen control. The activation segment is defined as the region Laboratory of Molecular Biophysics spanning conserved sequences DFG and APE and cor-and Oxford Centre for Molecular Sciences responds to residues 184-208 in cAPK (Taylor and Rad-University of Oxford zio-Andzelm, 1994). The activation segment includes Oxford OX1 3QUThr-197, one of two autophosphorylation sites in cAPK. United Kingd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,200
0
7

Year Published

1998
1998
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,302 publications
(1,233 citation statements)
references
References 37 publications
26
1,200
0
7
Order By: Relevance
“…All protein kinases possess an aspartic acid residue in subdomain VIb which is believed to be important as a catalytic base. Kinases that are known to be activated by phosphorylation, in general, possess a basic residue immediately preceding the catalytic aspartate (arginine\aspartate kinases) [39]. It has been suggested that RD kinases require neutralization of this basic residue by the incorporated phosphate to obtain the active conformation.…”
Section: Discussionmentioning
confidence: 99%
“…All protein kinases possess an aspartic acid residue in subdomain VIb which is believed to be important as a catalytic base. Kinases that are known to be activated by phosphorylation, in general, possess a basic residue immediately preceding the catalytic aspartate (arginine\aspartate kinases) [39]. It has been suggested that RD kinases require neutralization of this basic residue by the incorporated phosphate to obtain the active conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase activation in general is dependent upon the A or activating loop moving from an inactive to active conformation in order to uncover the kinase active site and to orientate key amino acids which catalyse substrate phosphorylation (see Johnson et al, 1996). Recently, mutations of c-fms and the closely related proto-oncogene c-kit have been identi®ed that change equivalent aspartate residues to valine within the activating loops of the M-CSF and SCF receptors.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the A-loop must undergo a large change in conformation for kinase activation to occur (Johnson et al, 1996). Consequently, it is suggested that downregulation of the M-CSF receptor and of tyrosine kinase receptors in general is normally initiated by some aspect or consequence of the change in conformation of the A-loop that is induced by ligand-binding.…”
Section: Discussionmentioning
confidence: 99%